Numerical Optimization to AI, and Back - Ravi, Sathya N. (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
The impact of numerical optimization on modern data analysis has been quite significant. Today, these methods lie at the heart of most statistical machine learning applications in domains spanning genomics, finance and medicine. The expanding scope of these applications (and the complexity of the associated data) has continued to raise the expectations of various criteria associated with the underlying algorithms. Broadly speaking, my research work can be classified into two AI categories: Optimization in ML (Opt-ML) and Optimization in CV (Opt-CV).